Analysis of Mathematical Misconceptions and Creative Thinking Skills among Seventh Grade Junior High Students - Dini Khirani; Zulfa Alya Nabilah Asha; Nazura Pretty Wafirah; Wita Tri Andini; Novferma Novferma; Husni Sabil (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2026)
This study aims to analyze the misconceptions experienced by seventh-grade students at SMP N 7 Muaro Jambi in learning mathematics, particularly on fractions, and to assess their mathematical creative thinking skills. The study employed a descriptive mixed-method approach using an essay test consisting of ten questions based on the Merdeka Curriculum. The participants were 30 seventh-grade students. The variables measured included four indicators of mathematical creative thinking skills: fluency, flexibility, originality, and elaboration. The data were analyzed descriptively to identify students’ levels of creative thinking skills and the types of misconceptions they experienced. The results showed that the average score of students’ mathematical creative thinking skills was 26.33, with the following distribution: 10% very creative, 3.33% creative, 3.33% fairly creative, 3.33% less creative, and 80% not creative. The most common misconceptions were found in addition and subtraction of fractions with different denominators and in converting mixed fractions into improper fractions. These findings indicate that most students still have difficulties understanding fundamental fraction concepts and applying creative problem-solving strategies. Therefore, mathematics instruction should emphasize conceptual understanding, provide varied learning activities, and encourage the continuous development of students’ mathematical creative thinking skills.